The Reflection of the Theory of Perception in a Unique Way in Artistic Creation - Allayarova Marhabo Mavlonovna (Periodica Journal, 2022)
The article analyzes the reflexive essence of the activity of the subject of artistic creation, reflecting in his own way. This form of reflection is a reflexive process by its nature, and it is revealed that it is an important aspect that ensures the integrative function of the mind of the subject of creation, which ensures that it acts outside the scope of its scale. The research of artistic creativity in the mentioned direction acquires important methodological importance in revealing the main factors of the social ideal, aesthetic ideas expressed in works of art, the motivation of people's activity and the status of spiritual values in it.
Keywords: perception; reflection; spiritual process; work of art